Reducing inappropriate testing in the diagnosis of the menopause and peri-menopause. (September 2016) - Williams, Jac; Currie, Heather; Foster, Adele; Anderson, Julia
The menopause should be diagnosed based on age, menstrual history and clinical symptoms, and as such, follicle stimulating hormone testing may be considered inappropriate when diagnosing the menopause or peri-menopause in women aged 45 and over. As part of a demand optimisation programme, the number of follicle stimulating hormone tests requested to diagnose the menopause in this age group was quantified and educational interventions were implemented to reduce inappropriate testing. The number of follicle stimulating hormone tests requested to diagnose the menopause in women aged 45 and over was successfully and sustainably reduced.